2018
DOI: 10.2217/bmm-2018-0048
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte to High-Density Lipoprotein Cholesterol Ratio in Patients With Diabetes Mellitus and Diabetic Nephropathy

Abstract: A total of 220 diabetes mellitus patients and 70 healthy controls were enrolled. There was no difference in an MHR between normoalbuminuric diabetic patients and the healthy controls. The MHR in patients with diabetic nephropathy was significantly higher than that of both the normoalbuminuric diabetic patients and the healthy controls. There was a significant positive correlation between urine albumin to creatinine ratio and the MHR. In multivariate linear regression analysis, the MHR was independently correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 29 publications
3
33
1
4
Order By: Relevance
“…This ratio has been widely used to assess the associations between IR and various clinical syn-dromes. Most previous studies on the relationship between TG/HDL-C and the incidence of T2DM reported a positive association [10,16,22], and similar results can be found for type 1 diabetes mellitus [23]. Our findings on TG/HDL-C are consistent with those studies.…”
Section: Discussionsupporting
confidence: 92%
“…This ratio has been widely used to assess the associations between IR and various clinical syn-dromes. Most previous studies on the relationship between TG/HDL-C and the incidence of T2DM reported a positive association [10,16,22], and similar results can be found for type 1 diabetes mellitus [23]. Our findings on TG/HDL-C are consistent with those studies.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies investigated the relationships between hematological parameters and the presence of degenerative complications in type 2 diabetes [ 3 , 6 8 , 11 , 13 – 15 , 17 , 18 ], but few explored their prognostic importance for adverse outcomes in longitudinal analyses [ 11 , 22 , 23 ]. Otherwise, these previous studies were mainly retrospective [ 11 , 22 ] and focused on specific hematological parameters, such as the NLR [ 11 , 22 ] and monocytes count [ 23 ], and in specific outcomes, such as cardiovascular events [ 11 ], renal function deterioration [ 22 ] and all-cause mortality [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…DM is characterized with chronic hyperglycemia that induces oxidative stress, and increased oxidative stress causes the most common microvascular complication of diabetes: DR. Our results suggest that increased MHR, as an inflammatory biomarker, contributes to the progression of chronic inflammation from initiation of diabetes to the progression of diabetic retinopathy. There is one study reported by Karataş et al (15) evaluating the relationship between MHR and diabetes mellitus and diabetic nephropathy. In their study, they showed the increased values of MHR in patients with diabetic nephropathy and its correlation with urine albumin to creatinine ratio.…”
Section: Discussionmentioning
confidence: 99%